2022
DOI: 10.1039/d1sc06157g
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-selective C–H arylation of phenols with N-carboxyindoles under Brønsted acid- or Cu(i)-catalysis

Abstract: Control over chemo- and regioselectivity is a critical issue in the heterobiaryl synthesis via C-H oxidative coupling. To address this challenge, a strategy to invert the normal polarity of indoles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…13 Many synthetic approaches have been developed to fabricate these diaryl compounds. 14 Despite its broad use, aryl–heteroaryl cross-coupling is limited to metal catalysis. 15 Although all these methods are effective, they often require multiple steps to prepare diverse reaction precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Many synthetic approaches have been developed to fabricate these diaryl compounds. 14 Despite its broad use, aryl–heteroaryl cross-coupling is limited to metal catalysis. 15 Although all these methods are effective, they often require multiple steps to prepare diverse reaction precursors.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although these advances have revolutionised the field of synthetic chemistry, to enable the rapid diversification of abundant starting materials, existing methods must use catalysts or prefunctionalized substrates, which are not always easily accessible due to their lack of availability in natural products. 6 These limitations led to serious constraints that made methods inapplicable to the late-stage functionalization of complex-substituted benzenes prevalent in bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other electron-rich (hetero) arenes, such as indoles, pyrroles, and benzofurans, failed to provide the corresponding coupled product, under both conditions (Scheme 78). 216 1.5.1.3 Photocatalysis. In the eld of bi-phenol synthesis via phenol-phenol homo-and cross-coupling, a novel oxidative photocatalytic protocol was reported by M. C. Kozlowski et al using MesAcr + BF 4 − as the photocatalyst.…”
Section: Arylationmentioning
confidence: 99%
“…[17] Other substrates for the C3-arylation of indoles include aryl chlorides and triflates, [18] benzoic acids, [19] arylhydrazines, [20] aryl diazonium salts, [21] polyhalo arenes, [22] cyclohexanones, [23] anisoles, [24] and phenols. [25] The C3-arylation of indoles has also been performed using an iridium catalyst [26] or even with no catalyst. [27] In 1985, Barton reported that the C3 phenylation of indole 1 could be accomplished using tetraphenylbismuth trifluoroace-tate 2 or para-toluenesulfonate 3 in refluxing benzene (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%